A Catheter-Related Bloodstream Infection by Brevibacterium casei in a Child with Acute Myeloid Leukemia: Case Report and Literature Review - Fumihiro Ochi; Hisamichi Tauchi; Kyoko Moritani; Shinobu Murakami; Hitoshi Miyamoto; Mayo Ueda; Kozo Nagai; Minenori Eguchi-Ishimae; Mariko Eguchi (Case Reports in Pediatrics)
The most common organisms isolated from pediatric catheter-related bloodstream infections (CRBSIs) are Gram-positive cocci, such as coagulase-negative staphylococci and Staphylococcus aureus. There are few formal reports of Brevibacterium casei infection and even fewer reports of CRBSI due to this Gram-positive rod. Here we report the first case of CRBSI due to B. casei in an 8-year-old girl with acute myeloid leukemia in Japan. The isolate exhibited decreased susceptibility to ß-lactam antibiotics. Antimicrobial therapy with meropenem and vancomycin, in addition to the removal of central venous catheter line, consequently led to a significant clinical improvement of the patient’s symptoms. A literature review found available clinical courses in 16 cases (4 pediatric cases including our case) of B. casei infection. Our case and those in literature suggested that B. casei infection often occurs in patients with indwelling central venous catheters; the literature review further suggested that removal of central venous catheters is required in most cases. Special attention should be paid to the detection of opportunistic infections due to Brevibacterium spp. in immunocompromized children who are using a central venous catheter.